Supplementation of Konjac Glucomannan into a Low-Fiber Chinese Diet Promoted Bowel Movement and Improved Colonic Ecology in Constipated Adults: A Placebo-Controlled, Diet-Controlled Trial - Chen, Hsiao-Ling; Cheng, Han-Chung; Wu, Wen-Tsu; Liu, Yann-Jiu; Liu, Su-Yuan (Journal of the American College of Nutrition, 2008)
OBJECTIVES: This diet-controlled study was designed to examine effects of konjac glucomannan (KGM) supplement on the bowel habits and colonic ecology in 7 constipated subjects. In addition, the mechanisms by which KGM modulated the bowel habit were explored. METHODS: Seven constipated subjects who passed bowel movement less than once a day participated in this diet-controlled linear study that consisted of a 21-d placebo period, a 7-d adaptation period, and a 21-d KGM-supplemented (1.5 g, tid) period. The large bowel response and fecal characteristics were recorded daily. Stools were collected individually on days 15-21 of placebo and KGM periods for analyses of colonic ecology indices such as fecal microflora, pH and short chain fatty acid content. Fecal component was determined to illustrate the fermentation of KGM. RESULTS: KGM supplement slightly but significantly increased the weekly defecation frequency from 4.1 ± 0.6 to 5.3 ± 0.6 and slightly eased the bowel movement. The fecal wet weight (g/d) and percent moisture were not significantly altered with the fiber supplement. However, the dry fecal weight (g/d) was increased mainly in the soluble mass. KGM supplement increased the fecal concentration (log counts/g wet feces) of lactobacilli, and the daily output (log counts/d) of bifidobacteria, lactobacilli and total bacteria in this diet-controlled study. In addition, fermentation of KGM resulted in greater fecal acetate, propionate and i-butyrate concentrations and lower fecal pH. CONCLUSION: The modest dose of KGM supplement promoted bowel movement by 30% and improved colonic ecology in constipated adults.